The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2021.606122
|View full text |Cite
|
Sign up to set email alerts
|

The Biomarker Potential of Caveolin-1 in Penile Cancer

Abstract: Various types of human cancers were characterized by an altered expression of epithelial or stromal caveolin-1 (CAV1). However, the clinical significance of CAV1 expression in penile cancer remains largely unknown. Here the expression patterns of CAV1 were analyzed in a retrospective cohort (n=43) of penile squamous cell carcinomas (SCC). Upon penile cancer progression, significantly increased CAV1-levels were determined within the malignant epithelium, whereas within the tumor stroma, namely the fibroblastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…Penile cancer is a rare, but aggressive cancer that disproportionally affects men in Africa, Asia, and South America 67,68 . Most penile cancers are squamous cell carcinomas, and risk factors include smoking and human papillomavirus (HPV) exposure, with approximately 50% of penile cancers being HPV + 69,70 . At the early stage of disease presentation, patients with penile cancer are treated with topical agents or surgical resection of local lesions.…”
Section: Act In Penile Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Penile cancer is a rare, but aggressive cancer that disproportionally affects men in Africa, Asia, and South America 67,68 . Most penile cancers are squamous cell carcinomas, and risk factors include smoking and human papillomavirus (HPV) exposure, with approximately 50% of penile cancers being HPV + 69,70 . At the early stage of disease presentation, patients with penile cancer are treated with topical agents or surgical resection of local lesions.…”
Section: Act In Penile Cancermentioning
confidence: 99%
“…67,68 Most penile cancers are squamous cell carcinomas, and risk factors include smoking and human papillomavirus (HPV) exposure, with approximately 50% of penile cancers being HPV + . 69,70 At the early stage of disease presentation, patients with penile cancer are treated with topical agents or surgical resection of local lesions. Patients with lymph node metastasis have a significantly worse prognosis and are treated with a lymph node surgical resection and systemic chemotherapy.…”
Section: Act In Penile Cancer Penile Cancer Background and Clinical Gapsmentioning
confidence: 99%
“…Several biomarkers for SCCP have been identified, although they are not routinely available in diagnosis and treatment. Panic et al demonstrated that the characteristic shift in stromalepithelial caveolin-1 (CAV1) was correlated with tumor progression in SCCP (14). Hu et al found that overexpression of inhibitor of DNA binding 1 (ID1) was significantly relevant to lymph node metastasis in SCCP (15).…”
Section: Introductionmentioning
confidence: 99%
“…Panic et al. demonstrated that the characteristic shift in stromal-epithelial caveolin-1 (CAV1) was correlated with tumor progression in SCCP ( 14 ). Hu et al.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed mechanisms behind tumor progression remain elusive. Although a recent genetic understanding of PSCC has shown that HRAS mutations, EGFR ampli cations, and dysregulation of CAV1 and IDO1 are associated with advanced disease [10][11][12], most studies lack speci c mechanisms owing to the lack of appropriate PSCC cell lines, convincing metastatic experiments in vivo and large-scale clinical validations. Our previous studies have established a molecular strati cation to predict high-risk PSCC patients with lymph node metastasis [13,14], but the mechanism needs to be further explored in depth.…”
mentioning
confidence: 99%